2013
DOI: 10.1186/1748-717x-8-203
|View full text |Cite
|
Sign up to set email alerts
|

Short–term effects of neoadjuvant chemoradiation therapy on anorectal function in rectal cancer patients: a pilot study

Abstract: BackgroundNeoadjuvant chemoradiation therapy followed by curative surgery has gained acceptance as the therapy of choice in locally advanced rectal cancer. However, deterioration of anorectal function after long-course neoadjuvant chemoradiation therapy combined with surgery for rectal cancer is poorly defined. The aim of this study was to evaluate the physiological and clinical change of anorectal function after neoadjuvant chemoradiation therapy for rectal cancer.MethodsWe analyzed 30 patients on whom preope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
1
8
1
Order By: Relevance
“…There are varying reports regarding the changes in manometric parameters between before and after PCRT. In some studies [ 19 , 20 ], SL increased as in the present study. In terms of pressure profiles, there have been contradictory reports [ 3 , 20 - 22 ].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…There are varying reports regarding the changes in manometric parameters between before and after PCRT. In some studies [ 19 , 20 ], SL increased as in the present study. In terms of pressure profiles, there have been contradictory reports [ 3 , 20 - 22 ].…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, a significant decrease in MTV was found subsequent to PCRT. Some studies [ 3 , 19 , 20 ] reported decreases in MTV after PCRT, but the differences were not statistically significant. Although some have also reported a decrease in rectal compliance [ 20 ], the present study did not find such a difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study considering the short-term preoperative change of anorectal function based on manometric data after nCRT, tumor response of chemoradiation was shown to be significantly associated with sensory threshold for desire to defecate and thus potential benefit of nCRT on defecatory function and local disease control has been suggested, at least in the short-term period after the radiation [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a novel objective method combined with the traditional questionnaire survey should be optimally applied to evaluate the change in anorectal function following rectal surgery. Anorectal manometry has been found to be an effective and objective test for evaluating postoperative anorectal function (15,16). We previously performed anorectal manometry combined with a questionnaire survey to evaluate the anorectal function of Chinese patients following partial intersphincteric resection and transanal endoscopic microsurgery (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%